Hubungan Rendaman Air Hangat dengan Garam dalam Pengurangan Bengkak Kaki pada Ibu Hamil - Amin Rahayu; Nevi Susianty (An-Najat, 2025)
Swelling of the legs in third trimester pregnant women can result in edema. Edema or swelling is a common condition experienced by pregnant women, especially in the second and third trimester. Edema can cause kidney failure, physical fatigue, chronic heart disease, joint disease, excessive salt intake. So that optimal healing is needed in pregnant women who experience edema. This type of research is descriptive with a case study approach. The research subjects were normal third trimester pregnant women conducted by Mrs. R at Pekanbaru Sejahtera Clinic. This research was conducted from June to July 2023. Data collection techniques used interviews, observations, physical examinations, and documentation studies. Data analysis compares theory with field practice. This study used primary data and secondary data. Based on the services performed, it was found that the foot swelling in Mrs. R had decreased. It is recommended for the mother to soak both feet for approximately 5 minutes.